Emergence and Epidemiology of Ciguatera in the Coastal Cities of Southern China - Chan, Thomas (Marine Drugs, 2015)
In the present review of 23 published case studies, the main objective is to report the emergence and epidemiology of ciguatera in the coastal cities of southern China. There was a sudden surge in ciguatera outbreaks in 2004. Ciguatera mostly occurred in the Guangdong Province. In Shenzhen, the incidence of ciguatera in 2004 was estimated to be over 7.5 per million people. In Foshan and Zhongshan, three large outbreaks each affecting over 100–200 subjects (caused by tiger grouper served at banquets) accounted for the much higher incidence of ciguatera in 2004 (>48.7 and >129.9 per million people). Humphead wrasse and areolated coral grouper were the other important ciguatoxic fish. In some subjects, risk factors for increased likelihood of (severe) ciguatera were present, namely concomitant alcohol consumption and ingestion of large reef fishes and CTX-rich fish parts. To prevent large outbreaks and severe illness, large apex predators from coral reefs should never be served at banquets and the public should realize the increased risk of severe symptoms due to ingestion of CTX-rich fish parts with alcohol. The systematic collection of accurate details, implementation of risk assessment process and continuing education for the public on prevention are of obvious importance.